Freezing Pressurized Water into a Standard Cylindrical Ice Sample in a Triaxial Cell - Baosheng Wang; Peixin Sun; Tingting Luo; Tao Zhang; Weihao Yang (Geofluids)
The mechanical characteristics of high-pressure frozen ice are a basis for the design of deep underground frozen walls, the drilling of thick permafrost and ice sheets, and the probing of extraterrestrial ice. The continuous control of the sample stress state from freezing to testing is essential for the experimental study of in situ mechanical response of high-pressure frozen ice. In the context, we developed a preparation technique for freezing pressurized water into a standard cylindrical ice sample in a triaxial cell. Through theoretical analysis, a cylindrical water sample with precise dimensions and strong sealing was fabricated using heat shrinkable tubing, sectional end caps, and an assembly cylinder. A mounting device was designed to insert the water sample into the triaxial cell without deformation. In order to deal with the lateral surface irregular of the resulting ice sample caused by freezing expansion, we proposed a pressurization method in which the volume of the confining medium is controlled to restrict the radial deformation of the sample, and the axial pressure on the sample is kept constant; thus, the freezing expansion will develop along the height direction through releasing the expansion pressure. Based on the analysis of sample deformation and finite element numerical simulations, the control method of the temperature fields of the sample and the confining medium was obtained, and the standard cylindrical ice sample which satisfies the geometric accuracy requirements was produced. The comparison of ice samples frozen by different freezing methods showed that the control of the confining medium mean temperature and the sample unidirectional freezing is necessary to improve the dimensional precision of the ice sample.